2012
DOI: 10.4315/0362-028x.jfp-12-072
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactic Acid Bacteria as a Biosanitizer To Prevent Attachment of Listeria monocytogenes F6900 on Deli Slicer Contact Surfaces

Abstract: The study was conducted to evaluate the attachment of three lactic acid bacteria (LAB) strains and their combination in a cocktail, to stainless steel coupons from a deli slicer, and their ability to inhibit the attachment of Listeria monocytogenes. In a previous study, three LAB strains, Pediococcus acidilactici, Lactobacillus amylovorus, and Lactobacillus animalis, were isolated from ready-to-eat meat and exhibited antilisterial effect. In the study reported here, hydrophobicity tests were determined accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Similarly, high antilisterial efficacy was achieved by pre-established biofilms of bacteriocin–producing LABs used as biosanitizers. Biofilm settlements of L. plantarum 35d in a small-scale model, as well as pretreatment with an LAB ( P. acidilactici , L. amylovorus , and L. animalis ) cocktail on SS coupons cut from the blade of a deli slicer machine, directly competed with L. monocytogenes for attachment to surfaces with a significant pathogen exclusion [ 113 , 114 ]. The probiotic strains L. paracasei and L. rhamnosus were reported to effectively inhibit biofilm formation by L. monocytogenes through the mechanisms of competition, exclusion, and displacement [ 115 ].…”
Section: Other Antimicrobial Interventionsmentioning
confidence: 99%
“…Similarly, high antilisterial efficacy was achieved by pre-established biofilms of bacteriocin–producing LABs used as biosanitizers. Biofilm settlements of L. plantarum 35d in a small-scale model, as well as pretreatment with an LAB ( P. acidilactici , L. amylovorus , and L. animalis ) cocktail on SS coupons cut from the blade of a deli slicer machine, directly competed with L. monocytogenes for attachment to surfaces with a significant pathogen exclusion [ 113 , 114 ]. The probiotic strains L. paracasei and L. rhamnosus were reported to effectively inhibit biofilm formation by L. monocytogenes through the mechanisms of competition, exclusion, and displacement [ 115 ].…”
Section: Other Antimicrobial Interventionsmentioning
confidence: 99%
“…In line with these above mentioned studies, different comparative studies have shown that the effectiveness of LAB against pre-formed biofilms of L. monocytogenes (approach known as displacement mechanism) is significantly lower than on adhesion and biofilm formation by competitive exclusion [ 158 , 159 , 160 ]. That is, acting early would seem to be most appropriate to prevent biofilm formation.…”
Section: Biosanitation Of L Monocytogenes Biofmentioning
confidence: 86%
“…This effect has been defined as competitive exclusion. As a result, a high number of different strains has been shown to be highly effective: Enterococcus durans [ 153 , 154 ], Enterococcus faecium [ 146 ], L. lactis [ 153 , 154 , 155 ], Lactobacillus plantarum and Enterococcus casseliflavus [ 156 ], Leuconostoc mesenteroides [ 157 ], L. sakei [ 150 , 158 ], Pediococcus acidilactici , Lactobacillus amylovorus and Lactobacillus animalis [ 159 ], Lactobacillus acidophilus , Lactobacillus casei , Lactobacillus paracasei and Lactobacillus rhamnosus [ 160 ], and Lactobacillus paraplantarum [ 161 ], among others.…”
Section: Biosanitation Of L Monocytogenes Biofmentioning
confidence: 99%
“…animalis, Lb. amylovorus, Pediococcus acidilactici) and found a succesful prevention of biofilm-forming Listeria monocytogenes, a food spoilage bacteria [13]. However, it should be noted that biofilm-forming LAB also caused notable cases like food spoilage and deterioration in food industry [14,15].…”
Section: Discussionmentioning
confidence: 99%